Assembling cultures : workplace activism, labour militancy and cultural change in Britain's car factories, 1945-82 - Saunders, Jack (Manchester scholarship online., 2019)
Assembling cultures takes a fine-grained look at workplace activism in car manufacturing between 1945 and 1982, using it as a key case for unpicking narratives around affluence, declinism and class. It traces the development of the militant car worker stereotype, looking at the social relations which lay behind the industry's reputation for conflict. This book reveals a changing, complex world of social practices, cultural norms, shared values and expectations. From the 1950s, car workers developed shop-floor organisations of considerable authority, enabling some new demands of their working lives, but constraining other more radical political aims. This is a story of workers and their place in the power relations of post-war Britain. This book is invaluable to academics and students studying the history, sociology and politics of modern Britain, particularly those with an interest in power, rationality, class, labour, gender and race.